Postnatal home visits by health extension workers in rural areas of Ethiopia: a cross-sectional study design - Yemane Berhane Tesfau; Alemayehu Bayray Kahsay; Tesfay Gebregzabher Gebrehiwot; Araya Abrha Medhanyie; Hagos Godefay (BMC, 2020)
Abstract Background In low-income countries like Ethiopia, where families have poor access to or do not utilize the services of formal health care systems, community health workers provide postnatal care services through home visits. However, the extent and effectiveness of home-based postnatal visits by community health workers such as the Ethiopian health extension workers (HEWs) are not well explored. This community -based study aimed to determine the coverage, contents of postnatal home visits and associated factors by health extension workers in Northern Ethiopia. Methods We conducted a community based cross-sectional study in the rural Districts in Northern Ethiopia from August to September 2018. A total of 705 mothers who gave a live birth in the year preceding the survey were selected using multistage random sampling. A structured questionnaire was applied to collect data by interviewing the mothers. Data were analyzed using SPSS version 22 statistical software. Association of postnatal home visits with possible explanatory variables was investigated using logistic regression. Results One hundred and two (14.5%) mothers and newborns received PNC home visit within three days after birth from HEW and 170(24.1%) reported postnatal home visits within 42 days. Among the mothers who received postnatal home visits, 6.5% measured their blood pressure, 11.2% measured their temperature, 20% counseled about family planning, 16.5% counseled on newborn danger signs, 11.2% counseled on the skin to skincare of the newborn and 14.1% of their newborns were measured their weight at home. Mothers who received at least one home visit during pregnancy (AOR, 7.49; CI 3.55-15.80), participated in pregnant women forum (AOR, 3.16; CI 1.67-5.99), notified their birth (AOR, 6.16; CI 3.50-10.84) and those members of community health insurance (AOR, 1.87; CI 1.13-3.10) were factors associated with postnatal home visit by a health extension worker. Conclusion The coverage of postnatal home visits by health extension workers remains low in rural districts of Northern Ethiopia. The existing health systems should consider interventions that improve pregnancy and birth notification strategies and more efforts should be made at improving community-based participation and linkages with community health workers.